Financial liberalization in ASEAN and the fisher hypothesis - Hook Law, Siong; Boon Tan, Hui; Ahmad Zubaidi Baharumshah, (Penerbit Universiti Kebangsaan Malaysia, 1999)
This study examines the long-run relationship between inflation and nominal interest raes in the 1990s by utilizing the Johansen-Juselius multivariate cointegration technique. The evidence supports the tax-adjusted form of Fisher hypothesis for three ASEAN countries, namely Singapore, Malaysia and Thailand. Thus, the assumption of a stable real interest rate appears to have empirical support for these low-inflation economies. We also demonstrate that inflation rate is both weakly and strongly exogenous in these three systems. However, the weak form of the hypothesis is decisively rejected for the inflation prone countries like the Philippines and Indonesia. In general, our results suggest that in a deregulated environments real interest rate is insulated from nominal shocks and money is neutral